2006
DOI: 10.1177/194589240602000113
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically Guided Aerobic Cultures in Postsurgical Patients with Chronic Rhinosinusitis

Abstract: Endoscopically guided aerobic cultures in postsurgical patients with acute exacerbations of chronic rhinosinusitis most commonly grew S. aureus, coagulase-negative staphylococci, and pseudomonal species. These cultures altered antibiotic treatment management decisions in a significant number of cases regardless of patients' clinical characteristics or history of previous culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…This may be because CoNS is not only the most common bacterial isolate in CRS in general, but also in subgroups of CRS, such as patients with a history of FESS. 12-15 Thus, the associations between the clinical factors and CoNS groups did not differ depending on the presence of nasal polyps or history of prior FESS. Therefore, it is appropriate to report combined results in Tables 2 and 3.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This may be because CoNS is not only the most common bacterial isolate in CRS in general, but also in subgroups of CRS, such as patients with a history of FESS. 12-15 Thus, the associations between the clinical factors and CoNS groups did not differ depending on the presence of nasal polyps or history of prior FESS. Therefore, it is appropriate to report combined results in Tables 2 and 3.…”
Section: Discussionmentioning
confidence: 81%
“…Several published studies looked at the presence of bacteria in postoperative sinus using endoscopically directed cultures, 12-15 and found that CoNS was one of the most common bacterial isolates in postoperative CRS patients. 12-15 In our study, 106 patients had CoNS as the sole positive culture result and 111 patients had CoNS as part of polymicrobial isolation, and thus, CoNS was also the most common bacterial isolate. The novelty of our study is that we analyzed the group of CRS patients with CoNS as the sole positive culture result separately.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have looked at the presence of bacteria in postoperative sinus descriptively, and S. aureus and P. aeruginosa were the most common isolates. 9,31 However, the effects of positive culture of S. aureus and P. aeruginosa in CRS remain unclear, because 20% of healthy subjects have persistent nasal carriage of S. aureus, and 60% have intermittent carriage. 32 Our study suggests that S. aureus and P. aeruginosa in CRS may be associated with different comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, bacterial and fungal cultures of nasal mucous secretions did reveal the presence of bacteria ( Pseudomonas and Acinetobacter ) as well as fungi ( Penicillium and Aspergillus ). Thus both patients had severe chronic rhinosinusitis most likely related to microbes (bacteria and fungi) detected in their water-damaged home [13, 5, 6, 23–25]. …”
Section: Ent Evaluationmentioning
confidence: 99%